Speech act theory and New Testament exegesis - Botha, J. (Hervormde teologiese studies, 1991)
Speech act theory offers New Testament exegesis some additional ways and means of approaching the text of the New Testament. This, the second in a series of two articles that make a plea for the continued utilisation and application of this theory to the text of the New Testament, deals with some of the possibilities and potential this theory holds for reading biblical texts. Advantages are pointed out and a few suggestions for the future proposed.